Differential impact of anemia in relation to sex in patients with myocardial infarction - Kanic, Vojko; Kompara, Gregor; Suran, David (Frontiers in Cardiovascular Medicine, 2023)
Background Data on the possible sex-specific effects of anemia on clinical outcome in patients with myocardial infarction are extremely sparse, conflicting, and inconclusive. We investigated the possible sex-specific effects of anemia on outcome in patients with myocardial infarction (MI) who underwent percutaneous coronary intervention (PCI). Methods Data from 8,318 patients, who were divided into four groups: men and women with and without anemia on admission, were analyzed. The association between anemia and sex and 30-day and long-term mortality was assessed. The median follow-up time was 7 years (25th, 75th percentile: 4, 11). Results Non-anemic men had the lowest 30-day and long-term observed mortality (4.3, 18.7%), followed by non-anemic women (7.0, 25.3%; p < 0.0001, p < 0.0001). Anemic men and women had similar mortality rates (12.8, 46.2%) and (13.4, 45.6%; p = 0.70, p = 0.80), respectively. The anemia/sex groups were independently associated with 30-day and long-term mortality (p = 0.033 and p < 0.0001, respectively). Compared to non-anemic men, non-anemic and anemic women had a similar risk of death at 30 days, but anemic men had a 50% higher risk of death (OR 1.12; 95% CI 0.83–1.52; p = 0.45, OR 1.30; 95% CI 0.94–1.79; p = 0.11, OR 1.50; 95% CI 1.13–1.98; p = 0.004, respectively). In the long term, anemic men had a 46% higher, non-anemic women 15% lower, and anemic women a similar long-term mortality risk to non-anemic men (HR 1.46; 95% CI 1.31–1.63; p < 0.0001, HR 0.85; 95% CI 0.76–0.96; p = 0.011, and HR 1.06; 95% CI 0.93–1.21; p = 0.37, respectively). Conclusion Our result suggests that the influence of anemia in patients with MI is different in men and women, with anemia seemingly much more harmful in male than in female patients with MI.